Boosted energy storage via carbon surface passivation. (15th November 2021) - Zhang, Yu; Zhao, Lianming; Wang, Xuyang; Wang, Xiaoning; Li, Honglin; Hu, Han; Fan, Zhuangjun; Xing, Wei; Yan, Zifeng
Abstract: The wide application of electric double layer capacitor (EDLC) is restricted by its low energy density. Such a bottleneck is hopefully tackled via engineering the carbon surface chemistry to kinetically inhibit the electrolyte decomposition and effectively extend the cell voltage of the EDLC. Here, we propose a facile carbon surface passivation strategy by rational functionalization with fluorine-containing functional groups. Evidenced by electrochemical measurements, the fluorinated activated carbon (F-AC) could tolerate a wider voltage window in commercially available organic electrolyte compared with the commercial activated carbon (AC). The theoretical simulation further verifies that the F-AC displays much increased activation energy for the formation of intermediate products, thereby dynamically hindering the electrolyte decomposition on the carbon surface. The F-AC based EDLC exhibits a remarkable voltage expansion from 2.7 V to 3.3 V and excellent cycling stability of 98.3% capacitance retention after 20000 cycles. A high energy density of 43.3 Wh kg −1 is achieved at the power density of 135 W kg −1, which is about 1.5-fold enhancement compared with the AC based counterpart, outperforming most of the reported organic EDLCs. These inspiring results bring fundamental insights into the regulation of voltage window, which will stimulate the design of high-performance energy storage devices. Graphical abstract: Image 1